Engineered proteins with sensing and activating modules for automated reprogramming of cellular functions - Jie Sun (Nature Portfolio, 2017)
Protein-based biosensors have been engineered to interrogate cellular signaling and manipulate function. Here the authors demonstrate iSNAP, a tool to detect tyrosine phosphorylation and activate desired protein enzymes allowing the control of phagocytosis in macrophages.